SEMA3A, a gene involved in axonal pathfinding, is mutated in patients with Kallmann syndrome. - Naresh Kumar Hanchate; Paolo Giacobini; Pierre Lhuillier; Jyoti Parkash; Cécile Espy; Corinne Fouveaut; Chrystel Leroy; Stéphanie Baron; Céline Campagne; Charlotte Vanacker; Francis Collier; Corinne Cruaud; et al. (PLoS Genetics)
Kallmann syndrome (KS) associates congenital hypogonadism due to gonadotropin-releasing hormone (GnRH) deficiency and anosmia. The genetics of KS involves various modes of transmission, including oligogenic inheritance. Here, we report that Nrp1(sema/sema) mutant mice that lack a functional semaphorin-binding domain in neuropilin-1, an obligatory coreceptor of semaphorin-3A, have a KS-like phenotype. Pathohistological analysis of these mice indeed showed abnormal development of the peripheral olfactory system and defective embryonic migration of the neuroendocrine GnRH cells to the basal forebrain, which results in increased mortality of newborn mice and reduced fertility in adults. We thus screened 386 KS patients for the presence of mutations in SEMA3A (by Sanger sequencing of all 17 coding exons and flanking splice sites) and identified nonsynonymous mutations in 24 patients, specifically, a frameshifting small deletion (D538fsX31) and seven different missense mutations (R66W, N153S, I400V, V435I, T688A, R730Q, R733H). All the mutations were found in heterozygous state. Seven mutations resulted in impaired secretion of semaphorin-3A by transfected COS-7 cells (D538fsX31, R66W, V435I) or reduced signaling activity of the secreted protein in the GN11 cell line derived from embryonic GnRH cells (N153S, I400V, T688A, R733H), which strongly suggests that these mutations have a pathogenic effect. Notably, mutations in other KS genes had already been identified, in heterozygous state, in five of these patients. Our findings indicate that semaphorin-3A signaling insufficiency contributes to the pathogenesis of KS and further substantiate the oligogenic pattern of inheritance in this developmental disorder.